Development of a Flexible and Conductive Heating Membrane via BSA-Assisted Electroless Plating on Electrospun PVDF-HFP Nanofibers - Mun Jeong Choi; Dae Hyeob Yoon; Yoo Sei Park; Hyoryung Nam; Geon Hwee Kim (Applied Sciences)
Planar heaters are designed to deliver uniform heat across broad surfaces and serve as critical components in applications requiring energy efficiency, safety, and mechanical flexibility, such as wearable electronics and smart textiles. However, conventional metal-based heaters are limited by poor adaptability to curved or complex surfaces, low mechanical compliance, and susceptibility to oxidation-induced degradation. To overcome these challenges, we applied a protein-assisted electroless copper (Cu) plating strategy to electrospun poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) nanofiber substrates to fabricate flexible, conductive planar heating membranes. For interfacial functionalization, a protein-based engineering approach using bovine serum albumin (BSA) was employed to facilitate palladium ion coordination and seed formation. The resulting membrane exhibited a dense, continuous Cu coating, low sheet resistance, excellent durability under mechanical deformation, and stable heating performance at low voltages. These results demonstrate that the BSA-assisted strategy can be effectively extended to complex three-dimensional fibrous membranes, supporting its scalability and practical potential for next-generation conformal and wearable planar heaters.